(3GdeMGcGI GdMGShHjI s - (3QaGg TgGH(B, (3GdMeOGfjs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2002)
(3GdJMdjd GdYOOj hGdeMGcGI,fWGb GdeMGcGI,WHjYI GdeMGcGI,GdGMJeGdGJ hGdJhRjYGJ GdGMJeGdjI,JhdjO GdCQbGe GdYThGFjI,GdMGSH GdQbej,feGPL JWHjbjI,JWHjbGJ GdeMGcGI Ydi GdHQGeL GdLGgRI,GdHQeLI HdZI (BPascals
(3HjHdjhZQGajG U(B.257s
Keywords: (3GdMGSHGJ GdGdcJQhfjIs; (3dZI (BPascals